UNIFORM SYSTEM OF ACCOUNTS OF THE FEDERAL POWER COMMISSION. - Smith, Charles W. (The Accounting Review, 1937)
The Uniform System of Accounts of the Federal Power Commission, which was adopted on June 16, 1936, was the result of a joint effort of the Federal Power Commission and representatives of several state commissions. The principle of original cost constitutes an entirely new conception of plant accounting for public utilities. It is so important to the needs of regulation and so misunderstood by those outside the pale of regulatory realms and so little has been written to explain its philosophy, that perhaps a rather full treatment of what it is and the reasons for its existence may not be altogether inappropriate. The importance of plant accounting for public utilities can hardly be overemphasized. Plant assets constitute about 86% of total assets of all electric utilities in the U.S. Another factor, which goes a long way towards explaining many problems and economic consequences identified with public utilities, is that the annual gross revenues of electric utilities amount, on an average, to only about 18% of the total investment in plant, so that the plant investment turns over about once in five and one-half years.